Systemic Immune Dysregulation, Complement Consumption, and Cryoglobulin Formation in Chronic Escherichia coli-Associated Urinary Tract Infection - Taki, Malaa M. (American Journal of Bioscience and Clinical Integrity, 2026)
Urinary tract infections caused by Escherichia coli are among the most common bacterial infections worldwide, and chronic and recurrent cases pose a significant clinical challenge. This study aimed to evaluate the immune profile of patients with chronic E. coli-induced urinary tract infections by measuring cryoglobulins, complement components (C3 and C4), C-reactive protein (CRP), and immunoglobulins (IgG and IgM), and comparing them with a control group of healthy individuals. A case-control study was conducted involving patients diagnosed with confirmed chronic urinary tract infections due to E. coli, with a control group of age- and sex-matched healthy individuals. Serum samples were collected and immunological markers were analyzed using standard laboratory techniques. The results showed a significant increase in CRP, IgG, and IgM levels in patients compared to the control group (P < 0.001). Conversely, a significant decrease in complement components C3 and C4 was observed in patients (P < 0.001). A higher percentage of cryoglobulin positivity was also found in the patient group, with a positive correlation between CRP and cryoglobulins, and an inverse correlation with complement levels. In conclusion, chronic urinary tract infections caused by E. coli indicate systemic immune activation, characterized by elevated inflammatory markers and immunoglobulins, along with complement component consumption and the appearance of cryoglobulins. These findings suggest that chronic bacterial infections can lead to systemic immune disturbances beyond the site of infection, potentially contributing to the use of these markers as biomarkers of disease severity.